(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
تضمنت الدراسة 54 مريضاً عولجوا في مشفى الأسد الجامعي في اللاذقية مصابين بفتق أُربي بين عامي1/10/ 2003-1/10/2004 ، لتقييم جدوى إعطاء الصادات وقائياً في جراحة ترميم الفتوق الأُربية صممت الدراسة بطريقة تقدمية عشوائية معماة بشكل مزدوج (PROSPEVTIVE RANDOMIZED-DOUBLE BLIND TEST) . قسم المرضى عند انتهاء الدراسة المرضى إلى مجموعتين متساويتين كل مجموعة 27 مريض: • تناولوا جرعة وحيدة وقائية (سيفوتكسيم). • تناولوا جرعة وحيدة من البلاسيبو. أجريت الجراحة تحت التخدير العام والتخدير القطني بنسبة 94.5% و5.5% على التوالي. استبعد جميع المرضى الذين لديهم أمراض مرافقة (سكري- أمراض قلبية – أمراض دم) والمرضى الذين عمرهم أكبر من 45 سنة، ووحدت العوامل التي يمكن أن تؤثر في نسبة ظهور الانتان مثل (طريقة الترميم - الخيوط المستخدمة – التعامل مع الجرح ). كانت المضاعفات بعد العمل الجراحي خمج مريض واحد في كلتي الفئتين أي بنسبة 3.7%. وعلى الرغم من عدم التوصل إلى فروق إحصائية واضحة بين المجموعتين ، نجد أن إعطاء الصادات في جراحة ترميم الفتوق الأُربية (المبرمجة وغير المختلطة) غير مبرر ولا يحمل فائدة لذلك نوصي بعدم استخدام الصادات. 54 patients have been treated at AL-Assad University Hospital in LATAKIA with complaint of groin hernia between [2003 and 2004] to evaluate the benefit of antibiotic prophylaxis after surgery for hernia repair, we have conducted a prospective randomized double blind test. At the end of this study the patients were divided into two equal groups 27 each (according to the antibiotic prophylaxis regime): A) group(b) 27 patent’s treated with cifotaxime. B) group(a) 27 patent’s received single dose of placebo. The operation was done under general and lumbar anesthesia 94% -and 5,5% respectively . Patients over 45 years were excluded, as well as patients with diabetes meleteus heart and blood disease. Factors that may play a role in the infection appearance were unified (repair method, used threads and dealing with the wound). One postoperative wound infection was found in both groups,(3,7%) even though no clear statistic differences between the two groups were obtained, so we advice that no benefit to give a prophylaxis antibiotic in surgery for hernia repair. we find that giving antibiotic prophylaxis in heresies repair surgery is unjustified unbeneficial, then we recommend not using antibiotic.